Injuries of Anterior Cruciate Ligament: A Review - Akhil, Jakkula; Ashok Sontakke, Yogesh (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2021)
The anterior cruciate ligament is an important structure maintaining knee stability. ACL injuries are very commonly seen. They cause substantial effect in the younger population, mainly seen in sports injuries either by contact or non-contact mode, affects productivity and physical activity after injury, causes economic burden of surgeries and rehabilitation and post-operative complications. They fail to heal owing to various factors such as a low number of cells, poor vascularity, the inhibitory effect of synovial fluid. Newer approaches to surgeries are evolving to provide better treatment. Hence, a review will enrich the understanding of the pattern of ACL injuries and its application in novel ways of surgical repair.